2013
DOI: 10.1016/j.jqsrt.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory retrieval and component investigations of the southern polar stratosphere based on high-resolution spectroscopy of the totally eclipsed moon surface

Abstract: a b s t r a c tIn this paper we present the high-resolution spectral observations of the fragment of lunar surface during the total lunar eclipse of December 10, 2011. The observations were carried out with the fiber-fed echelle spectrograph at the 1.2-m telescope in Kourovka Astronomical observatory (Ural mountains, central Russia). The observed radiation is transmitted by tangent trajectory through the southern polar stratosphere before the reflection from the Moon and the spectra contain a number of absorpt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The e=0.3 • model best matches the spectral features and slope of the e=0.38 • data, but is a factor of 4 larger in F in /F out . Indeed, aerosols and hazes will affect the eclipse brightness, especially for the smaller eclipse angles as has been shown before (Keen 1983;Ugolnikov et al 2013). Aerosols will be vertically stratified, and their absorption signal will depend on wavelength in a way that is difficult to anticipate.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The e=0.3 • model best matches the spectral features and slope of the e=0.38 • data, but is a factor of 4 larger in F in /F out . Indeed, aerosols and hazes will affect the eclipse brightness, especially for the smaller eclipse angles as has been shown before (Keen 1983;Ugolnikov et al 2013). Aerosols will be vertically stratified, and their absorption signal will depend on wavelength in a way that is difficult to anticipate.…”
Section: Discussionmentioning
confidence: 67%
“…Our measured value is slightly elevated above the mean background value 0.7 determined by Keen (1983), but is significantly lower than the values observed during eclipses that occurred soon after major volcanic eruptions (e.g., τ o−c = 2-6), and is consistent with the lack of recent major volcanic eruptions on Earth. See García and Ugolnikov et al (2013) for recent analyses of the impact of volcanic eruptions on the appearance of lunar eclipses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a "blue band" or "violet band" has been occasionally reported during other partial or total lunar eclipses. The monochrome version on the right used the Photoshop © "exclusion" density (0.27 g/cm 2 at 0.18 atm and 220 K) and scale height (2.0 km) of water vapor (Ugolnikov et al 2013 ).…”
Section: The Spectrum Of a Shadowmentioning
confidence: 99%
“…Vidal-Madjar et al (2010) observed the same partial lunar eclipse and found O 2 , O 3 and Na I based on the transmission spectrum obtained from the penumbral spectra. Ugolnikov et al (2013, hereafter U13) observed the total lunar eclipse in December 2011 with a resolving power of R ~30 000 and an SNR of 45 near the H α line and quantitatively analysed the atmospheric species, including O 2 , O 3 , H 2 O, O 2 · O 2 and NO 2 .…”
Section: Introductionmentioning
confidence: 99%